2019
DOI: 10.30958/ajms.5-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Financialization and Deindustrialization in the Southern European Periphery

Abstract: Historically, Southern European countries have shared a 'semi-peripheral' model of capitalism which has been characterized by fundamental fragilities in the production system. The financialization induced by the EMU has rendered these economies more fragile and unstable. Liberalization and market reform policies have taken southern economies onto the path of a credit-based and passively-extroverted financialized economy that trap them into a low-cost-of-wages search of competitiveness. However, the lack of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For the purpose of our argument, we assume that the various theoretical conceptualizations of globalization do not have much empirical effects in terms of threat generation, and this for three main reasons. First, there is an evidence that growing global financialization can bring adverse economic effects such as deindustrialization, unemployment and relative socio-economic deprivation (Kaya, 2012;Tori & Onaran, 2015;Gambarotto, Rangone & Solari, 2019), thus realistic threats (unemployment, relative deprivation) which all have the potential to generate compensatory responses, and, have we argue, especially among the youth. Second, as some political scientists argue, if globalism is not a phenomenon in and of itself, there is a growing prevalence of political discourses arguing for its existence and emphasizing its supposed effects and/or benefits.…”
Section: The Link Between Globalizations and Intercultural Relations)mentioning
confidence: 94%
See 1 more Smart Citation
“…For the purpose of our argument, we assume that the various theoretical conceptualizations of globalization do not have much empirical effects in terms of threat generation, and this for three main reasons. First, there is an evidence that growing global financialization can bring adverse economic effects such as deindustrialization, unemployment and relative socio-economic deprivation (Kaya, 2012;Tori & Onaran, 2015;Gambarotto, Rangone & Solari, 2019), thus realistic threats (unemployment, relative deprivation) which all have the potential to generate compensatory responses, and, have we argue, especially among the youth. Second, as some political scientists argue, if globalism is not a phenomenon in and of itself, there is a growing prevalence of political discourses arguing for its existence and emphasizing its supposed effects and/or benefits.…”
Section: The Link Between Globalizations and Intercultural Relations)mentioning
confidence: 94%
“…For the purpose of our argument, we assume that various theoretical conceptualizations of globalization do not have much empirical effects in terms of threat generation for three main reasons: First, there is evidence that growing global financialization can bring adverse economic effects such as deindustrialization, unemployment and relative social-economic deprivation (Gambarotto et al, 2018; Kaya, 2012; Tori & Onaran, 2015). These realistic threats have the potential to generate compensatory responses, especially among the youth.…”
Section: On Globalization and Globalismmentioning
confidence: 99%
“…In approaches from comparative and international political economy, the concept of financialization capitalizes on various visions of the evolution of world market economies (Lapavitsas and Powell, 2013; Nolke, 2016; Stockhammer, 2011). Concepts such as the financial turn of the economy (see Krippner, 2011), financial capitalism (Ertuk et al, 2008), subordinated (Lapavitsas and Powell, 2013), or semi-peripheral financialization (Becker, 2014; Gambarotto and Solari, 2015; Gambarotto et al, 2019; Rodrigues et al, 2016) emerged in scholarly literature, shedding light on how different national institutional systems and growth regimes interact with the expansion of finance and public/private indebtedness.…”
Section: State Financialization: Sovereign Debt Markets Derivatives A...mentioning
confidence: 99%
“…Batiston et al (2018) presented empirical evidence on the patterns of increasing financialization in the EU in the last two decades, an analysis of its possible adverse effects on several objectives of the EU 2030 agenda, including inclusive growth, innovation, inequality and financial stability. Gambarotto, Rangone and Solari (2019) suggested that liberalization and market reform policies have taken southern EU economies onto the path of a credit-based and passivelyextroverted financialized economy that trap them into a low-cost-of-wages search of competitiveness and deindustrialization. Svilokos and Burin (2017) tried to evaluate the process of financialization and its impact on the process of deindustrialization in the EU by detecting the significant and negative impacts of the process of financialization on value added of industry sector, as well as on the employment in the industry sector.…”
Section: Zaključekmentioning
confidence: 99%